Previsibilidade de retorno das ações no mercado brasileiro, através da aplicação de modelo de valor presente com retornos esperados constantes num contexto de expectativas racionais - Villarinho, Alvaro Teixeira (2005)
Using Brazilian financial data for some shares traded in the Brazilian Stock Market (BOVESPA) we test the expectation hypothesis of present value models discounted by a constant factor. This model relates the price of a stock to its expected dividends. To perform econometric testing we use mainly the jointly restriction through Wald Test in a Vector Autoregression framework, as well as alternative testing procedures. The empirical results partially support the present value model discounted by a constant factor to predict prices for stock through its expected dividends.